THE STRESS PROFILE OF EARLY CHILDHOOD EDUCATION TEACHERS DURING ONLINE LEARNING - Faqih Purnomosidi (UPI Kampus Cibiru, 2021)
This study aims to determine the description of stress in Early Childhood Education (ECE) teachers during online learning. The approach in this study was qualitative with a phenomenological method. The number of informants in this study was seven informants. The informants were preschool teachers who make online learning. Data collection was obtained through interviews and observations. The results showed that the stress symptoms experienced by informants were in the form of memory impairment, decreased concentration, quickly excessive anxiety, loss of interest, inability to relax, and trouble sleeping. The source of stress for each informant was making online learning videos during the pandemic and the depletion of economic, social, and psychological resources.